Intrinsic therapeutic and biocatalytic roles of ionic liquid mediated self-assembled platinum-phytase nanospheres - Soni, Sarvesh K.; Sarkar, Sampa; Selvakannan, P. R.; Sarkar, Dhiman; Bhargava, Suresh Kumar (RSC Advances, 2015)
We herein report the inherent antitumor efficiency of self-assembled phytase enzyme nanospheres and enhance their efficiency by decorating with platinum nanoparticles and with the anticancer drug curcumin. Firstly, controlled self-assembly of phytase enzyme in an Ionic Liquid 1-butyl-3-methylimidazolium tetrafluoroborate [Bmim][BF4], led to the formation of therapeutically active phytase nanospheres. These nanospheres were further decorated with platinum nanoparticles by adding the platinum ions to these spheres and the nanoparticles formation was mediated by the specific interaction between the histidine residue (in active site of phytase enzymes) and the platinum ions and subsequent reduction of the ions into nanoparticles. The enzyme spheres act as a functional soft template for the as-formed platinum nanoparticles. These Platinum decorated hybrid biomacromolecular phytase nanospheres were loaded with the anticancer drug curcumin and all the different kinds of nanospheres were subjected to in vitro cytotoxicity for their anticancer effect on three different kinds of cancer cell lines i.e. MCF-7, Hep-G2 and THP-1 derived human macrophages. We observed a gradual increase in the anticancer effect caused by only phytase nanospheres (25%), platinum-phytase nanospheres (37%), phytase-curcumin (78%) and platinum-phytase-curcumin nanospheres (90%) that establishes this protein based system as a robust combinatorial drug delivery vehicle. The platinum-phytase spheres also proved their usability as a highly efficient green and reusable biocatalytic system for phytate degradation. The present work facilitates our understanding of ionic liquid based synthesis for multifunctional protein based drug delivery vehicles incorporating combinatorial chemotherapy for potential application as biopharmaceutical agents for tumor treatment and bio-catalysis.